SISTEM PETUNGAN JAWA PADA MASYARAKAT DESA SUKOLILO, KECAMATAN SUKOLILO, KABUPATEN PATI - Nur Sitha Afrilia (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Petung Weton is a calculation system that is used by the society to determine special days in Javanese tradition. One of the days calculated for accuracy or compatibility is a wedding day in Sukolilo Village, Pati Regency. Based on that tradition, this study focuses on discussing of the calculation patterns that is applied in Sukolilo’s society. This study was written in a descriptive method and the data collection process was carried out by in-depth interview to main informants. The results of this study are conclusions related to the application of the calculation system (petung weton) in Sukolilo’s society today.